The evaluation of oxidative stress in lambs with Pestivirus infection - ASLAN Ο.; GENCAY GOKSU Α.; APAYDIN Ν. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study was carried out to measure the plasma malondialdehyde (MDA) level, and erythrocyte glutathione peroxidase (GSH-Px), catalase (CAT) and superoxide dismutase (SOD) activities in lambs with Pestivirus. Sixty lambs aged between 2.5-3 months old were included in the study. Blood and faeces samples were examined by reverse transcriptase-polymerase chain reaction (RT-PCR) test, using pan-Pestivirus primers. Clinical and virological examinations revealed that the numbers of non-infected and Pestivirus -infected animals were 20 (Group 1) and 40 (Group 2), respectively. Plasma MDA levels were found significantly higher in lambs with Pestivirus than that of controls (p<0.05) whilst the erythrocyte GSH-Px, CAT and SOD activities were significantly lower in lambs with Pestivirus (p<0.05) than in the controls. The determination of increased plasma MDA levels and decreased erythrocyte GSH-Px, CAT and SOD activities in the infected lambs confirms that oxidative stress is observed in Pestivirus. The presence of oxidative stress in Pestivirus indicates that the equilibrium between oxidants and antioxidants is shifted towards oxidants in lambs with Pestivirus.